Calcified pseudomeningocele of the lumbar spine: A review - Narverud, S.F.; Ramli, N.; Chandran, H.; Ganesan, D. (2013)
Purpose In this article, we review the English literature of calcified pseudomeningoceles in the lumbar region. Methods A systematic review using the Medline Database using the varied nomenclature for pseudomeningoceles, as well as reviewing the reference lists of relevant article found. Results We discuss the different pathological theories on formation of a pseudomeningocele, the formation of a calcified wall and the optimal management for this entity. To date, 17 cases have been described, of which 13 are reviewed here. Calcification of pseudomeningocele is a rare entity and in the lumbar spine this occurs postsurgically. The only predisposing factor is prior surgery to the lumbar spine. Computer tomography, magnetic resonance imaging (MRI) and MRI myelography in combination are the preoperative investigations of choice. The radiological work-up can be preoperatively diagnostic and is important in the surgical planning. Conclusions The treatment is surgicel removal and the decision to treat is based on patient symptoms and correlating these with imaging. There is an average reported follow-up of 1.7 years postoperatively for these patients and the reported outcome after surgery is good.